Cloning and in vitro Expression of N1 Neuraminidase Gene of Avian Influenza Virus A/Duck/Thailand/KU-KPS/2004(H5N1) - Alongkot Boonsoongnern; Thaweesak Songserm; Pariwat Poolperm; Amara Thongpan; Dhanirat Santivatr; Theerapol Sirinarumitr (Agriculture and Natural Resources, 2005)
Avian influenza virus (AIV) can spread rapidly and causes serious disease to animals and humans so it is crucial to have effective diagnostic tools for determining its existence. The purposes of this study were first, to clone N1 neuraminidase (NA) gene of AIV A/Duck/Thailand/KU-KPS/2004 (H5N1), and second, to express recombinant N1 using baculovirus expression system. Viral RNA extracted from positive AIV allantoic fluid was reverse-transcribed to cDNA and then was amplified by PCR using N1 specific primers. The PCR products approximately 1,300 bp that encode the N1 was introduced into baculovirus vector in order to allow N1 expression in insect cell lines. Immuno-dot blot analysis of crude extract of baculovirus infected insect cells using goat-anti H5N1 AIV hyperimmune serum gave a clear immunoreactive spot. SDS-PAGE analysis showed banding patterns from the crude extract contained major protein of 54 kDa. Western blot analysis using goat-anti H5N1 hyperimmune serum and mouseantihistidine monoclonal antibody also gave a specific band approximately the same size as that of SDSPAGE. Expression analysis of this gene indicated that recombinant neuraminidase may have correct post-translation modification and folding. The recombinant neuraminidase could be very useful for the development of a test kit that can differentiate infected from vaccinated animals (DIVA).